2022
DOI: 10.1021/acs.inorgchem.2c00897
|View full text |Cite
|
Sign up to set email alerts
|

Highly Electron-Doped TaON Single-Crystal Growth by a High-Pressure Flux Method

Abstract: Transition-metal oxynitrides have a variety of functions such as visible lightresponsive catalysts and dielectric materials, but acquiring single crystals necessary to understand inherent properties is difficult and is limited to relatively small sizes (<10 μm) because they easily decompose at high temperatures. Here, we have succeeded in growing platelet single crystals of TaON with a typical size of 50 × 100 × 10 μm 3 under a high pressure and high temperature (6 GPa and 1400 °C) using a LiCl flux. Such a ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…This indicates an upward shift of the valence band maximum due to the S-3p orbitals. Recently, BiS X ( X = Br and I) was reported to exhibit anodic photocurrent under visible light irradiation, which is promising for photovoltaic devices. , BiSF also shows n -type photocurrent when used it as photoelectrode in a solution of sacrificial agent (0.1 M NaI), consistent with observations in other bismuth mixed-anion compounds (Figure b). , The lower current density (335 μA cm –2 at 0.3 V vs Ag/AgCl) compared to BiSBr and BiSI may be ascribed to defects formed by high-pressure synthesis, which may trap photoexcited carriers . However, considering that the performance of photoelectrodes strongly depends on carrier transport, it is anticipated that improvements in electrode fabrication methods to reduce defects will pave the way for the development of efficient solar cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates an upward shift of the valence band maximum due to the S-3p orbitals. Recently, BiS X ( X = Br and I) was reported to exhibit anodic photocurrent under visible light irradiation, which is promising for photovoltaic devices. , BiSF also shows n -type photocurrent when used it as photoelectrode in a solution of sacrificial agent (0.1 M NaI), consistent with observations in other bismuth mixed-anion compounds (Figure b). , The lower current density (335 μA cm –2 at 0.3 V vs Ag/AgCl) compared to BiSBr and BiSI may be ascribed to defects formed by high-pressure synthesis, which may trap photoexcited carriers . However, considering that the performance of photoelectrodes strongly depends on carrier transport, it is anticipated that improvements in electrode fabrication methods to reduce defects will pave the way for the development of efficient solar cells.…”
Section: Resultsmentioning
confidence: 99%
“…37,38 The lower current density (335 μA cm −2 at 0.3 V vs Ag/AgCl) compared to BiSBr and BiSI may be ascribed to defects formed by high-pressure synthesis, which may trap photoexcited carriers. 39 However, considering that the performance of photoelectrodes strongly depends on carrier transport, it is anticipated that improvements in electrode fabrication methods to reduce defects will pave the way for the development of efficient solar cells.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The crystal size was gradually increased from 50–100 μm (1 h) to 100–300 μm (5 h) and 300–500 μm (8 h). Notably, the MnVO 3 crystals were grown under high pressure without any flux, unlike previous studies on high-pressure single crystal growth. …”
Section: Resultsmentioning
confidence: 99%
“…There are some previous reports of single crystal growth under high-pressure conditions by flux and hydrothermal methods and solid-state recrystallization, which mimic natural mineral occurrences. The maximum sizes of the obtained crystals were on the order of millimeters. Furthermore, a recent study reported that large single crystals of perovskite-type SrCoO 3 and BaFeO 3 were obtained by high-pressure treatment of single crystals of the ambient pressure precursor. , The development of single crystal growth techniques under high-pressure conditions is important for the precise study of new compounds.…”
Section: Introductionmentioning
confidence: 92%
“…6,7 Additionally, platelet TaON single crystals with a typical size of 50 × 100 × 10 μm 3 were grown by high-pressure flux methods using LiCl at a pressure of 6 GPa. 8 Single crystals of BaTaO 2 N and Sr 1−x Ba x TaO 2 N (0.04 ≤ x ≤ 0.23) with a maximum diameter of approximately 3 μm were grown from BaCN 2 fluxes, 9,10 which also acted as a nitrogen source. The ammonia (NH 3 )-assisted flux method has also been used to synthesize nanocrystals, such as BaTaO 2 N, BaNbO 2 N, CaTaO 2 N, SrTaO 2 N, and LaTaON 2 .…”
Section: Introductionmentioning
confidence: 99%